Pemanfaatan Limbah Kulit Buah Naga (Hylocereus costaricencis) sebagai Identifikasi Formalin/Boraks pada sediaan Makanan di Lingkungan Desa Tengah Pancur Batu - Ahmad Purnawarman Faisal; Adhisty Nurpermatasari; Riza Fahlevi Wakidi (Jurnal Abdi Masyarakat Kita, 2023)
The use of food additives (BTP) in the food production process needs to be jointly monitored, both by producers and by consumers. The impact of its use can be either positive or negative for the community. This community service activity uses the educational socialization method by conducting counseling and demonstrations on how to make a dragon fruit peel formalin spray kit as a simple way to identify formalin in food. The purpose of this community service is to find out whether waste from dragon fruit peel can be used as a test tool for the formalin content of food preparations in food preparations. The results of Community Service obtained a good knowledge category with the achievement of participants' knowledge levels before counseling and demonstration in the less (26.7%) sufficient (40%) and good (33.3) categories, after the extension the results of the category increased significantly, namely less 0 ( 0%), sufficient (13.4%), and good (86.6%).